2021
DOI: 10.1002/pbc.29056
|View full text |Cite
|
Sign up to set email alerts
|

Peptide receptor radionuclide therapy for treatment of metastatic neuroendocrine tumors in children

Abstract: Neuroendocrine tumors (NETs) of the pancreas and midgut are extremely rare in children, and patients presenting with metastatic disease have poor survival. Given this rarity, treatments are extrapolated from guidelines for adults with NET. Recent clinical trials in adults with NETs have shown that the addition of peptide receptor radionuclide therapy (PRRT) with 177 Lu-DOTATATE resulted in a disease control rate of nearly 80%, with minimal side effects. We report our experience using 177 Lu-DOTATATE to treat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Recently preliminary studies showed that PRRT-Lu is tolerable and feasible in pediatric patients with SSTR2-positive tumors. However, long-term efficacy and adverse effects in children are unknown [58].…”
Section: Which Is the Role Of Prrt-lu In Pediatric Population?mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently preliminary studies showed that PRRT-Lu is tolerable and feasible in pediatric patients with SSTR2-positive tumors. However, long-term efficacy and adverse effects in children are unknown [58].…”
Section: Which Is the Role Of Prrt-lu In Pediatric Population?mentioning
confidence: 99%
“…In children, there is no widespread experience in the treatment with PRRT-Lu, and the injected activities should be adapted per square meter [59,60]. In general, the same activity is used as in adults adapted to the weight with a maximum activity of 7.4 Gbq per infusion, with a total of four cycles every 8 weeks [58]. This unresolved question opens the need for further clinical trials PRRT-Lu in the pediatric population with GEP-NETs in which dosimetry data should be collected as well.…”
Section: Which Is the Role Of Prrt-lu In Pediatric Population?mentioning
confidence: 99%
“…For instance, the standard dose of 223 RaCl 2 used for treating bone metastases is 0.05 MBq/kg, 23,24 while the administered doses for β therapy drugs like 177 Lu-DOTATATE and 131 I-MIBG are significantly higher at 105.45 and 296 MBq/kg, respectively. 25,26 Considering the substantial difference in administered doses, the radiation exposure to personnel from 208 Tl remains lower than that from β emitters, such as 131 I and 177 Lu. 224 Ra can be obtained from the decay chain of the long-lived nuclides 232 Th(α) 228 Ra(β − ) 228 Ac(β − ) 228 Th(α) 224 Ra or 232 U-(α) 228 Th(α) 224 Ra.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, when 224 Ra is employed for α therapy, the administered dose will be relatively low due to the high lethality of α emitters to tumor cells. For instance, the standard dose of 223 RaCl 2 used for treating bone metastases is 0.05 MBq/kg, , while the administered doses for β therapy drugs like 177 Lu-DOTATATE and 131 I-MIBG are significantly higher at 105.45 and 296 MBq/kg, respectively. , Considering the substantial difference in administered doses, the radiation exposure to personnel from 208 Tl remains lower than that from β emitters, such as 131 I and 177 Lu.…”
Section: Introductionmentioning
confidence: 99%
“…Peptide receptor radionuclide therapy (PRRT) with 177 Lu-DOTATATE is a longstanding systemic treatment for metastatic gastroenteropancreatic neuroendocrine tumors (GEP-NET) [1][2][3]. Over recent years, several studies have reported remarkable results of individualized PRRT schemes for selected patients in different settings [4][5][6][7][8][9][10][11][12][13][14]. However, the only conducted randomized phase III trial (NETTER-1) demonstrating the efficacy of PRRT was limited to patients with midgut NET receiving a "standard treatment scheme" consisting of four cycles with a predefined administered activity of 7.4 GBq per cycle every 8 weeks [15].…”
Section: Introductionmentioning
confidence: 99%